Calibration of cosmogenic 36Cl production rates from Ca and K spallation in lava flows from Mt. Etna (38?N, Italy) and Payun Matru (36?S, Argentina) - GARRETA, VINCENT (My University, 2011)
Published cosmogenic 36Cl production rates from Ca and K spallation differ by almost a factor of 2. In this paper we determine production rates of 36Cl from Ca and K in samples of known age containing little Cl. Ca-rich plagioclases and K-feldspars were separated from a total of 13 samples collected on the surfaces of four basaltic lava flows at Mt. Etna (38?N, Italy) and from a trachyte lava flow at Payun Matru volcano (36?S, Argentina). Eruption ages, determined by independent methods, range between 0.4 and 32 ka. Sample site elevations range between 500 and 2500 m. Corresponding scaling factors were calculated using five different published scaling models, four of which consider paleo-geomagnetic field variations integrated over the exposure durations. The resulting five data sets were then analyzed using a Bayesian statistical model that incorporates the major inherent uncertainties in a consistent way. Spallation production rates from Ca and K, considering all major uncertainties, are 42.2 ? 4.8 atoms 36Cl (g Ca)-1a-1 and 124.9 ? 8.1 atoms 36Cl (g K)-1a-1 normalized to sea level and high latitude using the scaling method of Stone (2000). Scaling models that account for paleo-geomagnetic intensity changes yield very similar mean values (at most +4%). If the uncertainties in the independent ages are neglected in the Bayesian model, the calculated element specific production rates would be about 12% higher. Our results are in agreement with previous production rate estimations both for Ca and K if only low Cl (i.e. 20 ppm) samples are considered.
PUBLISHED
Keywords: Geology; Ca and K spallation; CI production rates